THE EFFECT OF BLOG MEDIA ON STUDENTS' KNOWLEDGE COMPETENCY IN HISTORY SUBJECTS: Pengaruh Media Blog terhadap Kompetensi Pengetahuan Siswa pada Mata Pelajaran Sejarah - Budiharto Sutoyo (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study aims to determine the effect of using blog media on students' knowledge competence in history subjects. This research used experimental method, type of quasi experiment with nonequivalent control group design. The research was conducted at SMA Negeri 2 Pontianak. The sampling technique used cluster sampling technique. Data collection techniques using tests with research instruments knowledge competency assessment sheet in the form of multiple choice questions. The statistical test results showed that there was abnormal data, so the statistical test used in this study was a nonparametric statistical test, U Mann Whitney. The statistical test results showed the posttest value of the experimental and control classes was 0.248. Because the value of Asymp. Sig. (2-tailed) > 0.05, then there is no effect of using blog media on students' knowledge competence in history subjects. It can be concluded that, there is a difference in the average value of the experimental class and the control class but there is no effect of using blog media in increasing students' knowledge competence in history subjects.